Controlling pea starch gelatinization behavior and rheological properties by modulating granule structure change with pea protein isolate - Jiwei Kuang; Wengang Zhang; Xijuan Yang; Ping Ma (Food Chemistry: X)
The purpose of this study was to investigate how the gelatinization behavior of pea starch (PS) was affected by pea protein isolate (PPI). The findings revealed that higher PPI levels decreased the swelling power of PS. Incorporating PPI raised the hot paste viscosity of PS, lowered the pasting temperature, and notably increased the gelatinization enthalpy according to differential scanning calorimetry analysis. Furthermore, the presence of PPI reduced the storage moduli of the starch paste, enhanced shear thinning behavior, and hindered starch molecular chain aggregation. With increasing PPI content from 0 to 12 %, amylose leaching and gel strength decreased by 25.6 % and 38.2 % respectively, indicating weak gel formation induced by PPI in PS. Confocal laser scanning microscopy confirmed that PPI envelopment of starch granules restricted their gelatinization by limiting granule swelling. These results carry significant implications for crafting pea-based foods with desired texture.